The Effects of Vocabulary Mastery on English-Speaking Ability: A Meta-Analysis Study - Helli Kristiana Br Bangun; Debora Chaterin Simanjuntak (Journal of Languages and Language Teaching, 2022)
The purpose of this meta-analysis is to analyse the effects of vocabulary mastery on English-speaking ability, which has been a extensively focused on English language teaching. A descriptive qualitative technique was utilized in this study. The data of this study consisted of 820 samples from 21 studies that focused on the correlation between students' sufficient academic vocabulary and English-speaking ability. The meta-analysis involves the studies conducted in Indonesia to draw deeper characteristics of the phenomena. The r and n were found in the data. n is the number of respondents, and r is the coefficient value. The researchers utilized five procedures to acquire the data: collecting studies or meta-analysis materials; calculating the effect size of each study; estimating the summary effect or mean effect size; analyzing the standard error; and evaluating publication bias. The data was analyzed with the help of JASP program. Because K = 21, 5K+10 Equals 115. The obtained fail-safe N value is 4727.000, with a significant target of 0.05 and p < 0.001. Because N > 5K+10 is a safe value, it is assumed that no publication bias exists in the Meta-Analysis study. In addition, the study's findings demonstrate that having an adequate academic vocabulary has a positive impact on English-speaking skills.